The Influence of Sensation Seeking, Travel Motivation and Social Media Networks towards Risk Perception among Malaysians to Travel Internationally - Ying Jia, Khor; Rahman, Suraiyati; Md Kassim, Normalini; Salman Shabbir, Muhammad (International Journal of Engineering and Technology, 2018)
The purpose of the present study was to investigate the influence of social media networks, travel motivation and personality traits in shaping the perception of risk among Malaysians intending to travel internationally. An online survey questionnaire was used to collect the data by sending an invitation to several travel websites. A total of 384 completed responses were considered valid to test the hypotheses through partial least squares structural equation modelling (PLS-SEM) by assessing the measurement approach and the structural model. The results indicated that competency or mastery factor and stimulus avoidance factor under travel motivation are perceiving risk positively while one could be risk aversion and another is risk seeker. And social media exerts significant positive relationship towards perceived risks; crime, health epidemics, political unrest, terrorism and disasters when travelling abroad. The findings in this study found that the ‘outbound’ traveler is not influenced by their personal traits towards perceived risk to travel abroad, but the influence of social media is undoubtedly a significant attribute in shaping their risk perception. The core drawback of this study is the use of online survey that restricted to respondent’s resources to reach IT access. The factor of sensation seeking appeared to be adversely related to travel risk perception. This result is distinct from the findings from previous studies that demonstrated and supported another possibility between this relationship.